Sequence and structural determinants of human APOBEC3H deaminase and anti-HIV-1 activities - Mitra, Mithun (Retrovirology, 2015)
BACKGROUND: Human APOBEC3H (A3H) belongs to the A3 family of host restriction factors, which are cytidine deaminases that catalyze conversion of deoxycytidine to deoxyuridine in single-stranded DNA. A3 proteins contain either one (A3A, A3C, A3H) or two (A3B, A3D, A3F, A3G) Zn-binding domains. A3H has seven haplotypes (I-VII) that exhibit diverse biological phenotypes and geographical distribution in the human population. Its single Zn-coordinating deaminase domain belongs to a phylogenetic cluster (Z3) that is different from the Z1- and Z2-type domains in other human A3 proteins. A3H HapII, unlike A3A or A3C, has potent activity against HIV-1. Here, we sought to identify the determinants of A3H HapII deaminase and antiviral activities, using site-directed sequence- and structure-guided mutagenesis together with cell-based, biochemical, and HIV-1 infectivity assays. RESULTS: We have constructed a homology model of A3H HapII, which is similar to the known structures of other A3 proteins. The model revealed a large cluster of basic residues (not present in A3A or A3C) that are likely to be involved in nucleic acid binding. Indeed, RNase A pretreatment of 293T cell lysates expressing A3H was shown to be required for detection of deaminase activity, indicating that interaction with cellular RNAs inhibits A3H catalytic function. Similar observations have been made with A3G. Analysis of A3H deaminase substrate specificity demonstrated that a 5′ T adjacent to the catalytic C is preferred. Changing the putative nucleic acid binding residues identified by the model resulted in reduction or abrogation of enzymatic activity, while substituting Z3-specific residues in A3H to the corresponding residues in other A3 proteins did not affect enzyme function. As shown for A3G and A3F, some A3H mutants were defective in catalysis, but retained antiviral activity against HIV-1vif (−) virions. Furthermore, endogenous reverse transcription assays demonstrated that the E56A catalytic mutant inhibits HIV-1 DNA synthesis, although not as efficiently as wild type. CONCLUSIONS: The molecular and biological activities of A3H are more similar to those of the double-domain A3 proteins than to those of A3A or A3C. Importantly, A3H appears to use both deaminase-dependent and -independent mechanisms to target reverse transcription and restrict HIV-1 replication. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12977-014-0130-8) contains supplementary material, which is available to authorized users.